2018
DOI: 10.5935/abc.20180108
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Induces Cardiomyocyte Apoptosis and Inhibits Cardiomyocyte Hypertrophy Via VEGFR-2 Signaling Pathway

Abstract: BackgroundPioglitazone has been widely used as an insulin-sensitizing agent for improving glycemic control in patients with type 2 diabetes mellitus. However, cardiovascular risk and protective effects of pioglitazone remain controversial.ObjectivesIn this study, we investigated whether pioglitazone affects cardiomyocyte apoptosis and hypertrophy by regulating the VEGFR-2 signaling pathway.MethodsCardiomyocytes were enzymatically isolated from 1- to 3-day-old Sprague-Dawley rat ventricles. Effects of pioglitaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…In vitro and in vivo observations showed pioglitazone to have anti-hypertrophic potential in cultured mice cardiomyocytes via inhibition of vascular endothelial growth factor (VEGF) [ 48 ] and inhibition of pressure overload-induced increases in cardiac wall thickness and myocyte diameter in wild-type mice. Moreover, it reduced the increase in the heart weight-to-body weight ratio in heterozygous non-diabetic PPAR-γ-deficient mice [ 49 ], suggesting PPAR-γ independent activity.…”
Section: Effects Of Pioglitazone On the Heartmentioning
confidence: 99%
“…In vitro and in vivo observations showed pioglitazone to have anti-hypertrophic potential in cultured mice cardiomyocytes via inhibition of vascular endothelial growth factor (VEGF) [ 48 ] and inhibition of pressure overload-induced increases in cardiac wall thickness and myocyte diameter in wild-type mice. Moreover, it reduced the increase in the heart weight-to-body weight ratio in heterozygous non-diabetic PPAR-γ-deficient mice [ 49 ], suggesting PPAR-γ independent activity.…”
Section: Effects Of Pioglitazone On the Heartmentioning
confidence: 99%
“…For pioglitazone, a study once reported that pioglitazone upregulated the levels of sphingomyelinase and ceramidase, a mediator of cardiomyocyte apoptosis (Baranowski et al, 2007). Moreover, by activating Bax and phosphorylated p53 as well as suppressing phosphorylated Akt and mTOR, pioglitazone could induce apoptosis in a VEGFR-2 dependent manner (Zhong et al, 2018).…”
Section: Antidiabetic Drugs (Rosiglitazone and Pioglitazone)mentioning
confidence: 99%
“…Pio, a peroxisome proliferator-activated receptor γ (PPARγ) agonist, displays protective roles in cardiovascular diseases. 5) Recently, Pio is reported to play an important role in ischemic heart disease, such as heart failure 6) and myocardial infarction. 7) However, the exact mechanism of Pio on apoptosis of myocardial cells induced via I/R injury has been rarely studied.…”
mentioning
confidence: 99%